PENGARUH LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR SUB SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA 2021-2022) - Nike Audina; Anne Putri; Aries Tanno; Hesi Eka Puteri; Imran Imran (Jurnal Akuntansi Kompetif, 2026)
This research aims to analyze the effect of liquidity on company value with profitability as a mediating variable (in manufacturing companies in the property and real estate subsector listed on the Indonesia Stock Exchange 2021-2022). The object of this research is companies in the property and real estate subsector listed on the Indonesia Stock Exchange during the period of 2021-2022. The research method used is quantitative with data analysis techniques using Structural Equation Modelling-Partial Least Square (SEM-PLS). The results of the study show that liquidity has a significant positive effect on company value, while profitability has an insignificant effect on company value, and profitability does not mediate the effect of liquidity on company value.